172k views
4 votes
Let f(x) = -2x + 4 and g(x) = -6x - 7. Find f(x) - g (x)I need help seeing the step by step steps for how to solve this.

Let f(x) = -2x + 4 and g(x) = -6x - 7. Find f(x) - g (x)I need help seeing the step-example-1

1 Answer

4 votes

Given:


\begin{gathered} f\mleft(x\mright)=-2x+4\ldots\ldots\ldots.(1) \\ g\mleft(x\mright)=-6x-7\ldots\ldots\ldots.(2) \end{gathered}

To find:


f\mleft(x\mright)-g\mleft(x\mright)

Substracting equation (2) from (1) we get,


\begin{gathered} f(x)-g(x)=-2x+4-(-6x-7) \\ =-2x+4+6x+7 \\ =4x+11 \end{gathered}

Thus, the answer is,


f(x)-g(x)=4x+11

User Chris Kobrzak
by
4.5k points